"Parents’ views Questionnaire for the education of emotions in Autism Spectrum Disorder" in a Greek context and the role of ICTs - Chaidi, Irene; Drigas, Athanasios (Technium Social Sciences Journal, 2022)
International research highlights the benefits of parental involvement in education [1] of children with ASD in parent behavioral training programs for children, and particular interest is the involvement of parents in socio-emotional learning programs, an area in which people with ASD, using serious serious digital games [2] and aiming for their emotional empowerment. This paper presents the results and their interpretation, as they emerged from the completion of a questionnaire regarding the views of parents’ participation in an educational intervention program to strengthen the emotional intelligence of people with ASD.